Automated high-content assay for compounds selectively toxic to Trypanosoma cruzi in a myoblastic cell line. - Julio Alonso-Padilla; Ignacio Cotillo; Jesús L Presa; Juan Cantizani; Imanol Peña; Ana I Bardera; Jose J Martín; Ana Rodriguez (Public Library of Science (PLoS), 2015)
BACKGROUND:Chagas disease, caused by the protozoan parasite Trypanosoma cruzi, represents a very important public health problem in Latin America where it is endemic. Although mostly asymptomatic at its initial stage, after the disease becomes chronic, about a third of the infected patients progress to a potentially fatal outcome due to severe damage of heart and gut tissues. There is an urgent need for new drugs against Chagas disease since there are only two drugs available, benznidazole and nifurtimox, and both show toxic side effects and variable efficacy against the chronic stage of the disease. METHODOLOGY/PRINCIPAL FINDINGS:Genetically engineered parasitic strains are used for high throughput screening (HTS) of large chemical collections in the search for new anti-parasitic compounds. These assays, although successful, are limited to reporter transgenic parasites and do not cover the wide T. cruzi genetic background. With the aim to contribute to the early drug discovery process against Chagas disease we have developed an automated image-based 384-well plate HTS assay for T. cruzi amastigote replication in a rat myoblast host cell line. An image analysis script was designed to inform on three outputs: total number of host cells, ratio of T. cruzi amastigotes per cell and percentage of infected cells, which respectively provides one host cell toxicity and two T. cruzi toxicity readouts. The assay was statistically robust (Z´ values >0.6) and was validated against a series of known anti-trypanosomatid drugs. CONCLUSIONS/SIGNIFICANCE:We have established a highly reproducible, high content HTS assay for screening of chemical compounds against T. cruzi infection of myoblasts that is amenable for use with any T. cruzi strain capable of in vitro infection. Our visual assay informs on both anti-parasitic and host cell toxicity readouts in a single experiment, allowing the direct identification of compounds selectively targeted to the parasite.